Isoallopregnanolone Inhibits Estrus Cycle-Dependent Aggressive Behavior - Torbjörn Bäckström; Sara K. S. Bengtsson; Jessica Sjöstedt; Evgenya Malinina; Maja Johansson; Gianna Ragagnin; Karin Ekberg; Per Lundgren (Biomolecules, 2023)
Among female rats, some individuals show estrus cycle-dependent irritability/aggressive behaviors, and these individual rats may be used as a model for premenstrual dysphoric disorder (PMDD). We wanted to investigate if these behaviors are related to the estrus cycle phase containing moderately increased levels of positive GABA-A receptor-modulating steroids (steroid-PAM), especially allopregnanolone (ALLO), and if the adverse behavior can be antagonized. The electrophysiology studies in this paper show that isoallopregnanolone (ISO) is a GABA-A-modulating steroid antagonist (GAMSA), meaning that ISO can antagonize the agonistic effects of positive GABA-A receptor-modulating steroids in both α1β2γ2L and α4β3δ GABA-A receptor subtypes. In this study, we also investigated whether ISO could antagonize the estrus cycle-dependent aggressive behaviors in female Wistar rats using a resident–intruder test. Our results confirmed previous reports of estrus cycle-dependent behaviors in that 42% of the tested rats showed higher levels of irritability/aggression at diestrus compared to those at estrus. Furthermore, we found that, during the treatment with ISO, the aggressive behavior at diestrus was alleviated to a level comparable to that of estrus. We noticed an 89% reduction in the increase in aggressive behavior at diestrus compared to that at estrus. Vehicle treatment in the same animals showed a minimal effect on the diestrus-related aggressive behavior. In conclusion, we showed that ISO can antagonize Steroid-PAM both in α1β2γ2L and α4β3δ GABA-A receptor subtypes and inhibit estrus cycle-dependent aggressive behavior.